Hepatocellular Carcinoma Intrinsic Cell Death Regulates Immune Response and Prognosis - De Re, Valli; Rossetto, Anna; Rosignoli, Alessandro; Muraro, Elena; Racanelli, Vito; Tornesello, Maria Lina; Zompicchiatti, Aron; Uzzau, Alessandro (Frontiers in Oncology, 2022)
Ablative and loco-regional treatment options, such as radiofrequency, ethanol injection, microwave and cryoablation as well as irreversible electroporation, are effective therapies for early-stage hepatocellular carcinoma (HCC). Hepatocytes death caused by ablative procedures is known to increase the release of tumor-associated antigen thus enhancing tumor immunogenicity. In addition, the heat ablative resection induces the pyroptotic cell death accompanied by the release of several inflammatory factors and immune-related proteins, including damage associated antigen patterns (DAMPs), heat shock proteins (HSP), ficolin 3, ATP and DNA/RNA, which potentiate the anti-tumoral immune response. Surgical approaches that enhance tumor necrosis and reduce hypoxia in the residual liver parenchyma have been shown to increase the disease-free survival rate by reducing the host’s immunosuppressive response. Scalpel devices and targeted surgical approach combined with immune modulating drugs are an interesting and promising area to maximize therapeutic outcomes after HCC ablation.